Sequencing of Zona Pellucida 4 (ZP4) Gene in Patients with Polycystic Ovary Syndrome Infected with Toxoplasmosis - Hanaa N. Abdullah (Journal of Global Pharma Technology, 2018)
Polycystic ovary syndrome is an endocrine disorder in women which leads to reproductive and metabolic abnormalities. The zona pellucida 4 gene is a glycoprotein which is a part of the extracellular matrix of an ovum. Twenty blood samples were taken from women with PCOS. Also, 20 blood samples were taken from the infected women, polycystic ovary with toxoplasmosis and healthy women groups. Whole blood samples were used to perform a polymerase chain reaction, while was ELISA used to measure Anti- Toxoplasma IgG antibody levels in the sera of both the studied and control groups. The biochemical test was used to determine the follicle-stimulating hormone, luteinizing hormone, and Testosterone. There is a highly significant difference regarding the levels of anti- Toxoplasma IgG antibody among PCOS patients who were infected with Toxoplasma gondii (1.5865±.42295), Toxoplssmosis control group (1.4097±.46171) and healthy control (6380±.33308). The hormones levels of PCOS showed a highly significant difference (P<0.01) FSH; (22.260±3.8692) compared with healthy control (8.362±1.1149) and Toxo. Control group LH; (32.080 ±2.7523), compared to Toxo. Control group (9.939±1.3910) and healthy control (9.445±1.8159) and Testosterone; (2.0470±.55663) compared to Toxo. The control group (.6580±.13575) and healthy control (.6365±.12512) respectively. Single nucleotide polymorphism T6235C indicated that T to C conversion was observed at nt 6325 in the ZP4 gene, and this evolution was experiential in one PCOS. This SNP is a synonymous substitution, which occurred in the fifth position of the proline codon, changing the codon ATA to ACA.